2014
DOI: 10.1002/eqe.2457
|View full text |Cite
|
Sign up to set email alerts
|

Seismic performance sensitivity and uncertainty analysis of gravity dams

Abstract: SUMMARYUncertainties in structural engineering are often arising from the modeling assumptions and errors, or from variability in input loadings. A practical approach for dealing with them is to perform sensitivity and uncertainty analysis in the framework of stochastic and probabilistic methods. These analyses can be statically and dynamically performed through nonlinear static pushover and IDA techniques, respectively. Of the existing structures, concrete gravity dams are infrastructures which may encounter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(28 citation statements)
references
References 36 publications
0
28
0
Order By: Relevance
“…Considering the RTR variability in the IDA capacity functions, they should be summarized using some central values like the mean, median, and 16% and 84% fractiles. [47], (c) gravity dam [48], (d) gravity dam [49], (e) gravity dam [43], (f) arch dam [50], (g) gravity dam [51], and (h) gravity dam [52]. PGA, peak ground acceleration.…”
Section: Incremental Dynamic Analysismentioning
confidence: 99%
“…Considering the RTR variability in the IDA capacity functions, they should be summarized using some central values like the mean, median, and 16% and 84% fractiles. [47], (c) gravity dam [48], (d) gravity dam [49], (e) gravity dam [43], (f) arch dam [50], (g) gravity dam [51], and (h) gravity dam [52]. PGA, peak ground acceleration.…”
Section: Incremental Dynamic Analysismentioning
confidence: 99%
“…However, the model was too simple to present seismic failure of the intake tower. Alembagheri and Ghaemian (2012, 2013, 2015 used incremental dynamic analysis (IDA) to determine the seismic performance and different limit states of hydraulic structures, such as gravity and arch dams. For PBSD, IDA (Vamvastsikos 2002) is an emerging method that offers a thorough estimation of the seismic demand and limit state capacity of a structure.…”
Section: Introductionmentioning
confidence: 99%
“…A vector IM would contain more information about the ground motion than a scalar IM, and it has been shown that it is more effective in predicting the response of building frames and bridges [11][12][13][14][15][16][17]. Probabilistic seismic assessment of concrete dams using single-valued IMs has been well performed [18][19][20][21], but such study employing vector-valued IMs is very scarce.…”
Section: Introductionmentioning
confidence: 99%